Linkages and key factors between soil bacterial and fungal communities along an altitudinal gradient of different slopes on mount Segrila, Tibet, China - Ma, Tiantian; Zhang, Xinjun; Wang, Ruihong; Liu, Rui; Shao, Xiaoming; Li, Ji; Wei, Yuquan (Frontiers in Microbiology, 2022)
Soil microbes are of great significance to many energy flow and material circulation processes in alpine forest ecosystems and their distribution pattern along altitudinal gradients is an essential research topic for the Tibetan Plateau. Yet our understanding of linkages between soil microbial communities and key factors along an altitudinal gradient of differing slopes remains limited. Here, the diversity, composition and interaction of bacterial and fungal communities and in response to environmental factors were compared across five elevation sites (3500 m, 3700 m, 3900 m, 4100 m, 4300 m) on the eastern and western slopes of Mount Segrila, by using Illumina MiSeq sequencing. Our results showed that microbial community composition and diversity were distinct at different elevations, being mainly influenced by soil total nitrogen and carbonate. Structural equation models indicated that elevation had a greater influence than slope upon the soil microbial community. Co-occurrence network analysis suggested that fungi were stable but bacteria contributed more to among interactions of bacterial and fungal communities. Ascomycota was identified as a key hub linking microbial–soil and biotic–internal interactions, which might affect the soil microbial co-occurrence network resilience of alpine forest ecosystems on the Tibetan Plateau.